Incontinence, bladder neck mobility, and sphincter ruptures in primiparous women - Jundt K; Scheer I; Schiessl B; Karl K; Friese K; Peschers UM (European Journal of Medical Research, 2010)
Abstract Objective To compare the function of the pelvic floor in primiparae before and during pregnancy with the status post partum concerning symptoms of incontinence, sphincter ruptures, bladder-neck mobility and the influence of the different modes of deliveries. Methods Questionnaire evaluating symptoms of urinary and anal incontinence in nulliparous women before and after delivery and correlating these symptoms with functional changes of the pelvic floor based on a careful gynaecologic examination as well as perineal and endoanal ultrasound. Results 112 women were included in our study and came for the first visit, 99 women returned for follow-up 6 months after childbirth. Stress and flatus incontinence significantly increased from before pregnancy (3 and 12%) to after childbirth (21 and 28%) in women with spontaneous delivery or vacuum extraction. No new symptoms occurred after c-section. There was no significant difference between the bladder neck position before and after delivery. The mobility of the bladder neck was significantly higher after vaginal delivery using a vacuum extraction compared to spontaneous delivery or c-section. The bladder neck in women with post partum urinary stress incontinence was significantly more mobile than in continent controls. The endoanal ultrasound detected seven occult sphincter defects without any correlation to symptoms of anal incontinence. Conclusion Several statistically significant changes of the pelvic floor after delivery were demonstrated. Spontaneous vaginal delivery or vacuum extraction increases the risk for stress or anal incontinence, delivery with vacuum extraction leads to higher bladder neck mobility and stress incontinent women have more mobile bladder necks than continent women.